Peer Group Proximity and Self-Esteem Among Bully Adolescents in Buleleng and Jembrana Regency - Putu Sukma Megaputri; Ni Luh Putu Erna Purnama Wardani; Dewi Aprelia Meriyani; Bayu Oka Widiarta (Faculty of Nursing, Universitas Jember, 2021)
Background: Bullying can be a mental problem for adolescents that has an impact on psychological disorders to suicide, not only for the victim but also for the bully. Handling the impact of bullying so far has only focused on victims, attention should also be directed to bully, because bully is the main actor in the occurrence of bullying. Purpose: To analyze the relationship between self-esteem and peer group proximity with bully behavior among adolescents in Buleleng and Jembrana. Methods: Quantitative research with a cross-sectional approach, samples were taken from junior high school students in Buleleng and Jembrana Districts. The measuring instrument used a questionnaire to screen adolescents who tend to be bully, a self-esteem questionnaire, a peer group closeness questionnaire and a bully behavior questionnaire. The number of samples in this study were 78 people taken by stratified random sampling technique. Univariate analysis was carried out to determine the sociodemographic characteristics of the respondents, then the analysis of the relationship between self-esteem and bully behavior used Rank Spearman as well as the relationship between peer group proximity and bully behavior. Results: Self-esteem has a significant relationship with p <0.05, r = -0.867 with teenage bullying. Peer group closeness has a significant relationship with p <0.05, r = -0.556 with bully behavior. Conclusion: Self-esteem and peer group proximity are significantly associated with bullying behavior. The higher the level of self-esteem and peer group closeness, the lower the bullying's behavior.